Corduroy - Freeman, Don 1908-1978. (New York Scholastic Inc., 1968)
A toy bear in a department store wants a number of things, but when a little girl finally buys him he finds what he has always wanted most of all.
Keywords: Toys -- Fiction; Fantasy; Picture books